Superior carbon belts from Spirogyra for efficient extracellular electron transfer and sustainable microbial energy harvesting. Issue 12 (6th March 2019) - Shi, Yu-Tong; Yu, Yang-Yang; Xu, Zi-Ai; Lian, Jiabiao; Yong, Yang-Chun
Abstract : Superior carbon belts from Spirogyra were explored for highly efficient extracellular electron transfer and microbial energy harvesting. Abstract : Microbial fuel cells (MFCs) showed great potential to harness sustainable electric energy from wastewater. Exploration of natural and high-performance electrode materials was highly required to overcome the big challenge of sustainability for microbial energy harvesting with MFCs. In this study, Spirogyra, a wide-spread biopollutant, was explored as a superior material to fabricate high performance and sustainable electrodes for MFCs. By simple carbonization, tens of centimeters long and conductive carbon belts with a self-constructed carbon nanoparticle coating were synthesized from Spirogyra filaments. Impressively, the carbon belts formed 3D non-woven interconnected macroporous networks with intriguing features of light weight and high biocompatibility. More strikingly, they activated highly efficient extracellular electron transfer due to excellent cell/electrode interaction, which is usually not achievable by conventional carbon electrodes. Consequently, Spirogyra electrodes outperformed other natural material derived or commercial electrodes in MFCs, suggesting that Spirogyra was the most superior natural material for sustainable electrodes, which provides new opportunities for more sustainable energy harvesting with MFCs.